A swamp of non-SUSY vacua. (November 2017) - Danielsson, U.; Dibitetto, G.; Vargas, S.
Abstract We consider known examples of non-supersymmetric AdS7 and AdS4 solutions arising from compactifications of massive type IIA supergravity and study their stability, taking into account the coupling between closed- and open-string sector excitations. Generically, open strings are found to develop modes with masses below the Breitenlohner-Freedman (BF) bound. We comment on the relation with the Weak Gravity Conjecture, and how this analysis may play an important role in examining the validity of non-supersymmetric constructions in string theory.